2017
DOI: 10.1039/c6cc09200d
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic blinking of red fluorescent proteins for super-resolution microscopy

Abstract: Single-molecule localization microscopy relies on either controllable photoswitching of fluorescent probes or their robust blinking. We have found that blinking of monomeric red fluorescent proteins TagRFP, TagRFP-T, and FusionRed occurs at moderate illumination power and matches well with camera acquisition speed. It allows for super-resolution image reconstruction of densely labelled structures in live cells using various algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The partial reversibility of the red form's decay, as observed after the activation, could be attributed to its mixed photobleaching mechanism, which combines both reversible and permanent components. RFPs generally undergo reversible transitions to dark states [52][53][54], which is part of the photobleaching that takes place during fluorescent imaging (these are usually visible at the early phase of the probe photobleaching). Thus, while the reversibility of the chemical red-to-blue conversion after the reductant is washed off could be attributed to the chromophore's re-maturation, the reversibility observed after the dithionite-free "photoconversion" is most likely associated with the red form returning to a bright state.…”
Section: Discussionmentioning
confidence: 99%
“…The partial reversibility of the red form's decay, as observed after the activation, could be attributed to its mixed photobleaching mechanism, which combines both reversible and permanent components. RFPs generally undergo reversible transitions to dark states [52][53][54], which is part of the photobleaching that takes place during fluorescent imaging (these are usually visible at the early phase of the probe photobleaching). Thus, while the reversibility of the chemical red-to-blue conversion after the reductant is washed off could be attributed to the chromophore's re-maturation, the reversibility observed after the dithionite-free "photoconversion" is most likely associated with the red form returning to a bright state.…”
Section: Discussionmentioning
confidence: 99%
“…53 Since such conformational switches are often energetically controlled, the excitation dependence of kGSR may originate from the absorption of the excitation photons by dark state species and/or the rise of local temperature due to high irradiance. 28,52,54 FusionRed and its sibling TagRFP-T exhibit fluorescence intermittency in live-cell imaging using TIRF microscopy with camera acquisition timescales of 50 ms. 55 The study demonstrated the potential to achieve a theoretical spatial resolution beyond the diffraction limit (~25-30 nm) with FusionRed using SMLM methods like BALM and SOFI. 55 In our previous work, we developed FusionRed-MQV, a FusionRed variant with 3-fold higher molecular brightness developed using a combination of lifetime-based microfluidic selection and site-directed mutagenesis.…”
Section: Introductionmentioning
confidence: 89%
“…28,52,54 FusionRed and its sibling TagRFP-T exhibit fluorescence intermittency in live-cell imaging using TIRF microscopy with camera acquisition timescales of 50 ms. 55 The study demonstrated the potential to achieve a theoretical spatial resolution beyond the diffraction limit (~25-30 nm) with FusionRed using SMLM methods like BALM and SOFI. 55 In our previous work, we developed FusionRed-MQV, a FusionRed variant with 3-fold higher molecular brightness developed using a combination of lifetime-based microfluidic selection and site-directed mutagenesis. 53 Additionally, we found that the substitution C159V in FusionRed resulted in a brighter variant which showed a monoexponential photobleaching trace contrary to the biexponential behavior exhibited by the parental RFP FusionRed.…”
Section: Introductionmentioning
confidence: 89%
“…We have previously reported that TagRFP and several closely related red fluorescent proteins exhibit fast reversible photoconversion between dark and bright states, which could be utilized for super-resolution imaging [8]. We, therefore, sought to assess the photoconversion in a closely related fluorescent proteinTagBFP [4], which is a blue-emitting variant of TagRFP.…”
Section: Biophotonics In Cancer Researchmentioning
confidence: 99%